The influence of different ethnicity in Malaysia on parental preference towards behaviour management techniques in paediatric dentistry - Rahman, Md Toufiqur (2022)
Uncooperative or disruptive behaviour can interfere with quality of care, increase the length of treatment time and increase risk of injury to the child. The challenge of treating children who are unable or unwilling to cooperate has led to the development of a variety of behaviour management techniques. The aim of this study is to assess the parental acceptance of different behaviour management techniques (BMT) used during dental treatment of children in three major ethnic group (Malay, Indian and Chinese) of Malaysia. This was a cross-sectional comparative study involving convenient sampling method, using a sample of 72 parents attending Paediatric Dentistry Clinic, Hospital USM and Klinik Pergigian UKM, Universiti Kebangsaan Malaysia. A videotape presentation was produced to demonstrate ten of the AAPD approved BMTs to the selected parents in the following order: TSD, VC, Modelling, PR, Distraction, PP/A, HOM, NO, OS and GA. Statistical analyses was done for descriptive statistics such as mean values, standard deviations, standard errors and coefficients of variation were measured. Multiple comparisons were done by One Way Anova with Post-Hoc analysis and Fisher Extract test. Among 72 parents, 43 were males and 29 were female parents. With respect to ethnicity Malay (50%) were more when compared to Chinese (25%) and Indian (25%). However, parents with college degree (48.6%) was found to be more with income range 2001-5000 RM (55.6%).Further, a higher mean was reported in tell-show-do (93.47±14.26) method of behaviour management technique, followed by audio-visual (81.94±18.05), parental presence/absence (73.89±22.62). There was no statistically significant difference among all the independent ethnic groups with p-value > 0.05 except modelling technique which showed a significant difference with p-value 0.047. There was statistically significant difference between three groups when compared to modelling BMT. Post Hoc Analysis with multiple comparisons by Bonferroni, only comparison between Chinese and Indian shown statistically significant mean difference (p- Value=0.047). We conclude that tell-show-do, distraction, modelling, parental presence/ absence has been shown to produce similarly acceptable results amongst Malaysian parents with statistically insignificant differences in the amount of approval given for the techniques. Physical restraint, oral sedation and general anesthesia were the least approved in the current study.